Water quality of the Athabasca oil sands area Vol I ... - Akena, A. M. (University of Alberta Library, 1980)
This report documents locations of Athabasca Oil Sands area water quality sampling sites; sampling, analytical and quality control methods used; the volume and availability of assembled data; and an extensive appraisal of the quality of the data base. The quality control measures taken proved to be very useful in identifying causes of variations in analytical data and, as far as this water quality data base is concerned, in producing valid and accurate data. ...